Regions That Work : How Cities and Suburbs Can Grow Together - Jr., Manuel Pastor (Book collections on Project MUSE., 2000)
Regions That Work provides a history and critique of community-development corporations, a statistical analysis of the poverty-growth relationship in seventy-four metro areas, a detailed study of three regions that have produced superior equity outcomes, and a provocative call for new policies and new politics."A remarkable and timely book. ... Must reading." William Julius Wilson.